Implementasi dan dampak pendidikan holistik berbasis lingkungan pada siswa: studi kasus di sekolah alam - Widodo, Syukri Fathudin Achmad; MR, Moh Irsyad Fahmi; Widiastuti, Anik; Ahmed, Touheed; Shahzeb, Shahzeb (Universitas Negeri Yogyakarta, 2024)
This study investigates the implementation of holistic education at Sekolah Alam Sukahaji in Tasikmalaya and how it impacts student development. The study used a qualitative case study design and employed participant observation, in-depth interviews, and document analysis. Data were collected over a period of six months from various stakeholders, including teachers, parents, and students. The results showed that Sekolah Alam Sukahaji successfully integrated the national curriculum with a nature-based learning approach and the institution's core values. Sekolah Alam Sukahaji created a learning environment that supports the overall growth of students by using an experiential learning model and the surrounding environment as a medium for learning. This model has been shown to improve students' cognitive, affective, and psychomotor abilities. The active involvement of parents in the learning process reinforces the idea that education is holistic and has a positive impact on students' cognitive and socio-emotional development. Thus, Sekolah Alam Sukahaji offers a viable option for the education system and contributes significantly to the diversification of learning methods and education models in Indonesia.